Platinum-Halloysite nanoclay nanojets as sensitive and selective mobile nanosensors for mercury detection - Maric, Tijana (2021)
Naturally available tubular Halloysite nanoclay is modified with platinum for the fabrication of autonomous self-moving nanojets. The nanojets exhibit great performance in the removal of heavy metal ions in aqueous solutions. The heavy metal ions get readily adsorbed onto the large surface area available on the Halloysite nanoclay. The fabricated nanojets are observed to have a greater efficiency with sensing of larger sized metal ions (Hg2+ and Pb2+) as compared to smaller sized ions (Zn2+ and Cd2+), and especially sensitive toward the “detection” of mercury ions. The proposed system displays a wide detection range (0.25–1000 ppb). Moreover, the system displays high sensitivity with low limit of detection (3.24 ppb) achieved, which falls in the permissible range for mercury in drinking water (2–5.5 ppb) as set by the World Health Organisation. The self-moving nanojets serve as mobile nanosensors for the simultaneous detection and removal of heavy metals in aqueous samples.